Pengaruh Harga Dan Loyalitas Terhadap Keputusan Pembelian Studi Kasus Pada Gratis Ongkir Lazada Di Kota Bekasi - Nadia Intana Sari; Vigo Satrio (JAMBIS : Jurnal Administrasi Bisnis, 2026)
Abstract. The rapid growth of e-commerce encourages companies to implement effective marketing strategies through pricing and the enhancement of customer loyalty to influence purchasing decisions. Free shipping programs are one of the strategies used by Lazada to attract consumers. This study aims to analyze the effect of price and loyalty on purchasing decisions of Lazada consumers in Bekasi City. The method used is quantitative with a survey approach using questionnaires, and the data are analyzed through multiple linear regression with t-test, F-test, and coefficient of determination. The results show that price has a positive and significant effect on purchasing decisions with a t-value of 3.820, a significance value of 0.000, and a regression coefficient of 0.244. Loyalty also has a positive and significant effect with a t-value of 3.437, a significance value of 0.001, and a regression coefficient of 0.276. Simultaneously, price and loyalty have a significant effect on purchasing decisions with an F-value of 36.211 and a significance value of 0.000. The coefficient of determination (R²) of 0.516 indicates that 51.6% of purchasing decisions are influenced by price and loyalty, while the remaining percentage is influenced by other factors outside this study. Keywords: Price, Loyalty, Purchasing Decision, Free Shipping, Lazada